Composite oxide and method for producing same

A composite oxide of cerium, zirconium, and aluminum, optionally with a rare earth metal, is produced to address the heat resistance issue of CeO2-ZrO2-Al2O3-based oxides, maintaining high specific surface area and oxygen storage capacity under high-temperature exhaust gases, thus improving exhaust gas purification catalysts.

JP7621384B2Active Publication Date: 2025-01-24MITSUI MINING & SMELTING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022571969
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-11-17
Publication Date
2025-01-24
Estimated Expiration
2041-11-17

AI Technical Summary

Technical Problem

Cerium oxide (CeO2)-Zirconium oxide (ZrO2)-Aluminum oxide (Al2O3)-based composite oxides require further improvement in heat resistance to maintain their specific surface area and oxygen storage capacity under high-temperature exhaust gas conditions.

Method used

A composite oxide containing cerium, zirconium, and aluminum elements, optionally with a rare earth metal, is produced through a method involving the preparation of a raw material liquid, precipitation of a mixed oxide, and subsequent calcination to achieve a specific surface area of 60.0 m^2/g after heat treatment at 1000°C, with controlled ratios and phases to enhance heat resistance and oxygen storage capacity.

Benefits of technology

The composite oxide maintains a high specific surface area and exhibits excellent heat resistance and oxygen storage capacity even under high-temperature exhaust gas conditions, enhancing the performance of exhaust gas purification catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621384000001
    Figure 0007621384000001
  • Figure 0007621384000002
    Figure 0007621384000002
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a cerium oxide (CeO2)-zirconium oxide (ZrO2)-aluminum oxide (Al2O3) composite oxide which has improved heat resistance; and a method for producing this composite oxide. The present invention provides a composite oxide which contains cerium element, zirconium element and aluminum element, and optionally a rare earth metal element other than cerium element, and which has a specific surface area of 60 m2 / g or more as determined by a BET method after a heat treatment at 1,000°C in the atmosphere for 25 hours. The present invention also provides a method for producing this composite oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite oxide containing elemental cerium, elemental zirconium and elemental aluminum, and a method for producing said composite oxide. [Background technology]

[0002] Exhaust gas emitted from internal combustion engines of automobiles, motorcycles, etc. contains harmful components such as hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx), etc. Three-way catalysts, which have catalytic activity to oxidize HC and CO and convert them into water and carbon dioxide, and reduce NOx and convert it into nitrogen, are used as exhaust gas purification catalysts to purify and detoxify these harmful components.

[0003] In order to mitigate the fluctuation of oxygen concentration in exhaust gas and efficiently purify HC, CO, NOx, etc., a material having oxygen storage capacity (OSC) (hereinafter sometimes referred to as "OSC material"), for example, a powder of a cerium oxide (CeO2)-zirconium oxide (ZrO2) based composite oxide, is used as a constituent material of the three-way catalyst. Note that the expression "oxygen storage and release capacity" is sometimes used in this specification, but "oxygen storage and release capacity" is synonymous with "oxygen storage capacity."

[0004] In order to improve the exhaust gas purification performance of exhaust gas purification catalysts, it is necessary to improve the heat resistance of OSC materials and enable them to maintain their specific surface area even when exposed to high-temperature exhaust gas.

[0005] As a technique for improving the heat resistance of OSC materials, a technique is known in which aluminum element is added to a cerium oxide (CeO2)-zirconium oxide (ZrO2)-aluminum oxide (Al2O3)-based composite oxide (e.g., Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-268470 A [Patent Document 2] Special Publication No. 2014-534938 [Patent Document 3] Special Publication No. 2014-522801 [Patent Document 4] Special Publication No. 2015-521538 Summary of the Invention [Problem to be solved by the invention]

[0007] However, there is a demand for further improvement in the heat resistance of cerium oxide (CeO2)-zirconium oxide (ZrO2)-aluminum oxide (Al2O3) based composite oxides.

[0008] Therefore, an object of the present invention is to provide a cerium oxide (CeO2)-zirconium oxide (ZrO2)-aluminum oxide (Al2O3) based composite oxide having improved heat resistance and a method for producing said composite oxide. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides a composite oxide containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, which has a specific surface area of ​​60.0 m or less as measured by the BET method after heat treatment at 1000° C. for 25 hours in air. 2 / g or more.

[0010] The present invention also provides a method for producing a pharmaceutical composition comprising the steps of: (a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt; (b) adding a precipitating agent to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (c) calcining the precipitate to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a composite oxide, comprising: 50 is 1 nm or more and 220 nm or less. Effect of the Invention

[0011] According to the present invention, there are provided a cerium oxide (CeO2)-zirconium oxide (ZrO2)-aluminum oxide (Al2O3) based composite oxide having improved heat resistance and a method for producing said composite oxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described below. In this specification, unless otherwise specified, "rare earth metal element" means a rare earth metal element other than cerium element, "rare earth metal ion" means a rare earth metal ion other than cerium ion, "water-soluble rare earth metal salt" means a water-soluble rare earth metal salt other than water-soluble cerium salt, and "poorly water-soluble rare earth metal salt" means a poorly water-soluble rare earth metal salt other than poorly water-soluble cerium salt. In addition, in this specification, "cerium oxide" means CeO2, "zirconium oxide" means ZrO2, and "aluminum oxide" means Al2O3.

[0013] <Complex oxide> The composite oxide of the present invention contains elemental cerium, elemental zirconium, elemental aluminum, and optionally a rare earth metal element other than elemental cerium.

[0014] The composite oxide of the present invention may be in the form of, for example, powder.

[0015] From the viewpoint of improving the oxygen storage capacity of the composite oxide, the amount of cerium element contained in the composite oxide of the present invention, calculated as cerium oxide, is preferably 1.0 mass % or more and 50 mass % or less, more preferably 3.0 mass % or more and 40 mass % or less, and even more preferably 5.0 mass % or more and 30 mass % or less, based on the mass of the composite oxide of the present invention.

[0016] From the viewpoint of improving the heat resistance of the composite oxide, the amount of zirconium element contained in the composite oxide of the present invention, calculated as zirconium oxide, is preferably 1.0 mass % or more and 70 mass % or less, more preferably 10 mass % or more and 60 mass % or less, and even more preferably 20 mass % or more and 45 mass % or less, based on the mass of the composite oxide of the present invention.

[0017] The mass ratio of the amount of zirconium element converted into zirconium oxide to the amount of cerium element converted into cerium oxide is preferably 0.10 or more and 20 or less, more preferably 0.70 or more and 10 or less, and even more preferably 1.3 or more and 5.0 or less, from the viewpoint of balancing the oxygen storage capacity and heat resistance of the composite oxide.

[0018] From the viewpoint of improving the heat resistance of the composite oxide, the amount of aluminum element contained in the composite oxide of the present invention, calculated as aluminum oxide, is preferably 20 mass% or more and 90 mass% or less, more preferably 30 mass% or more and 80 mass% or less, even more preferably 40 mass% or more and 70 mass% or less, and even more preferably 40 mass% or more and 60 mass% or less, based on the mass of the composite oxide of the present invention.

[0019] The mass ratio of the amount of aluminum element, calculated as aluminum oxide, to the total amount of the amount of cerium element, calculated as cerium oxide, and the amount of zirconium element, calculated as zirconium oxide, is preferably 0.10 or more and 9.0 or less, more preferably 0.50 or more and 4.0 or less, even more preferably 0.60 or more and 2.3 or less, and even more preferably 0.60 or more and 1.9 or less, from the viewpoint of balancing the oxygen storage capacity and heat resistance of the composite oxide.

[0020] The composite oxide of the present invention may contain one, two, three or more kinds of rare earth metal elements other than elemental cerium.

[0021] The rare earth metal elements other than cerium element can be selected from, for example, yttrium element, praseodymium element, scandium element, lanthanum element, neodymium element, samarium element, europium element, gadolinium element, terbium element, dysprosium element, holmium element, erbium element, thulium element, ytterbium element, lutetium element, etc. For example, the composite oxide of the present invention can contain one, two, or three or more rare earth metal elements selected from lanthanum element, neodymium element, praseodymium element, and yttrium element.

[0022] The amount of rare earth metal elements other than cerium contained in the composite oxide of the present invention in terms of oxide (when the composite oxide of the present invention contains two or more rare earth metal elements other than cerium, the total amount of the oxide-equivalent amounts of the two or more rare earth metal elements) is preferably 0.1 mass% or more and 30.0 mass% or less, more preferably 1.0 mass% or more and 25.0 mass% or less, and even more preferably 5.0 mass% or more and 20.0 mass% or less, based on the mass of the composite oxide of the present invention, from the viewpoint of improving the oxygen storage capacity and heat resistance. Note that the oxides of rare earth metal elements other than cerium are sesquioxides (Ln2O3, where Ln represents a rare earth metal element) except for praseodymium oxide and terbium oxide, and praseodymium oxide is usually Pr6O 11 and terbium oxide is usually Tb4O7.

[0023] In the composite oxide of the present invention, the cerium element and the zirconium element may form a solid solution phase (for example, a solid solution phase of cerium oxide and zirconium oxide) together with the oxygen element. The cerium element and the zirconium element may form, together with the oxygen element, a single phase (a single cerium oxide phase, a single zirconium oxide phase) which is a crystalline phase or an amorphous phase, in addition to the solid solution phase.

[0024] In the composite oxide of the present invention, the aluminum element may form a solid solution phase together with the cerium element and / or zirconium element and the oxygen element (for example, a solid solution phase of cerium oxide, zirconium oxide, and aluminum oxide, a solid solution phase of cerium oxide and aluminum oxide, or a solid solution phase of zirconium oxide and aluminum oxide) or may form a single phase (single aluminum oxide phase) which is a crystalline phase or an amorphous phase together with the oxygen element.

[0025] In the composite oxide of the present invention, the rare earth metal element other than cerium may form a solid solution phase together with cerium and / or zirconium and oxygen (for example, a solid solution phase of cerium oxide, zirconium oxide, and an oxide of a rare earth metal element other than cerium, a solid solution phase of cerium oxide and an oxide of a rare earth metal element other than cerium, or a solid solution phase of zirconium oxide and an oxide of a rare earth metal element other than cerium), or may form a single phase (an oxide of a rare earth metal element other than cerium) which is a crystalline phase or an amorphous phase together with oxygen.

[0026] The oxide-equivalent amounts of various metal elements contained in the composite oxide of the present invention can be calculated, for example, by measuring the amounts of various metal elements in a molten product obtained by dissolving the composite oxide of the present invention by alkali fusion or the like using a conventional method such as inductively coupled plasma atomic emission spectrometry (ICP-AES), and then calculating from the measured amounts of various metal elements.

[0027] The specific surface area of ​​the composite oxide of the present invention measured by the BET method after heat treatment in air at 1000° C. for 25 hours is preferably 60.0 m 2 / g or more. After heat treatment in air at 1000°C for 25 hours, the specific surface area measured by the BET method is 60.0 m 2 A composite oxide having a specific surface area of ​​1000 nm or more has excellent heat resistance and can maintain its specific surface area even when exposed to high-temperature exhaust gas.

[0028] In a preferred embodiment, the amount of aluminum element contained in the composite oxide of the present invention calculated as aluminum oxide is 60 mass % or less based on the mass of the composite oxide of the present invention, and the specific surface area of ​​the composite oxide of the present invention measured by the BET method after heat treatment in air at 1000° C. for 25 hours is 60.0 m 2 / g or more. Although the amount of aluminum element contained in the complex oxide in terms of aluminum oxide is 60 mass% or less based on the mass of the complex oxide, the complex oxide has excellent heat resistance and can maintain its specific surface area even when exposed to high-temperature exhaust gas. From the viewpoint of improving the heat resistance of the complex oxide, the amount of aluminum element contained in the complex oxide in terms of aluminum oxide is preferably 20 mass% or more, more preferably 30 mass% or more, and even more preferably 40 mass% or more based on the mass of the complex oxide.

[0029] The specific surface area of ​​the composite oxide of the present invention measured by the BET method after heat treatment in air at 1000° C. for 25 hours is more preferably 60.5 m 2 / g or more, and even more preferably 61.0m 2 / g or more, and even more preferably 61.5m 2 / g or more, and even more preferably 62.0m 2 The upper limit of the specific surface area of ​​the composite oxide of the present invention measured by the BET method after heat treatment in air at 1000° C. for 25 hours is not particularly limited. 2 / g, 90.0m 2 / g or 80.0m 2 / g.

[0030] The specific surface area is measured according to "(3.5) Multipoint method" in "6.1 Quantitative method" of JIS R1626:1996 "Method for measuring specific surface area of ​​fine ceramic powder by gas adsorption BET method". Nitrogen, an adsorption gas, is used as the gas, and five points are measured within the equilibrium relative pressure range of 0.05 to 0.35. For example, the "BELSORP-miniX" manufactured by Microtrack Bell is used as the measuring device.

[0031] The composite oxide of the present invention is made to support 1 part by mass of rhodium element in terms of metal per 100 parts by mass of the composite oxide, and then heat-treated in air at 1000°C for 25 hours to prepare a sample. The oxidizing power of the composite oxide measured using the samples at 300°C, 400°C, and 500°C is the oxidizing power of the composite oxide (300°C), the oxidizing power of the composite oxide (400°C), and the oxidizing power of the composite oxide (500°C), respectively, the composite oxide of the present invention is (A) The oxidation power of the composite oxide (300°C) is 1400 or more; (B) The oxidation power of the composite oxide (at 400°C) is 2600 or more. (C) The oxidation power of the composite oxide (500°C) is 2800 or more. It is preferable that one or more of the following conditions are satisfied. A composite oxide that satisfies one or more of the following conditions (A) to (C) has excellent heat resistance and can exhibit excellent oxygen storage capacity even after being exposed to high-temperature exhaust gas.

[0032] In a preferred embodiment, the amount of aluminum element contained in the complex oxide of the present invention calculated as aluminum oxide is 60% by mass or less based on the mass of the complex oxide of the present invention, and the complex oxide of the present invention satisfies one or more of (A) to (C). The complex oxide according to this embodiment has excellent heat resistance and can exhibit excellent oxygen storage capacity even after being exposed to high-temperature exhaust gas, even though the amount of aluminum element contained in the complex oxide calculated as aluminum oxide is 60% by mass or less based on the mass of the complex oxide, from the viewpoint of improving the heat resistance of the complex oxide. The amount of aluminum element contained in the complex oxide according to this embodiment calculated as aluminum oxide is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more based on the mass of the complex oxide.

[0033] In a further preferred embodiment, the amount of aluminum element contained in the composite oxide of the present invention calculated as aluminum oxide is 60 mass % or less based on the mass of the composite oxide of the present invention, and the specific surface area of ​​the composite oxide of the present invention measured by the BET method after heat treatment in air at 1000° C. for 25 hours is 60.0 m 2 / g or more, and the composite oxide of the present invention satisfies one or more of (A) to (C). The composite oxide according to this embodiment has an aluminum oxide-equivalent amount of the aluminum element contained in the composite oxide of 60 mass% or less based on the mass of the composite oxide, but has excellent heat resistance and can maintain its specific surface area even when exposed to high-temperature exhaust gas, and can exhibit excellent oxygen storage capacity even after exposure to high-temperature exhaust gas. From the viewpoint of improving the heat resistance of the composite oxide, the aluminum oxide-equivalent amount of the aluminum element contained in the composite oxide according to this embodiment is preferably 20 mass% or more, more preferably 30 mass% or more, and even more preferably 40 mass% or more based on the mass of the composite oxide.

[0034] The complex oxide oxidizing power (300° C.) is preferably 1400 or more, more preferably 1600 or more, and even more preferably 1800 or more. The upper limit of the complex oxide oxidizing power (300° C.) is not particularly limited, and is, for example, 3100.

[0035] The complex oxide oxidizing power (400° C.) is preferably 2600 or more, more preferably 2700 or more, and even more preferably 2800 or more. The upper limit of the complex oxide oxidizing power (400° C.) is not particularly limited, and is, for example, 3100.

[0036] The complex oxide oxidizing power (500° C.) is preferably 2800 or more, more preferably 2850 or more, and even more preferably 2900 or more. The upper limit of the complex oxide oxidizing power (500° C.) is not particularly limited, and is, for example, 3100.

[0037] The sample used for measuring the oxidizing power of the complex oxide is prepared by supporting 1 part by mass of rhodium element, calculated as metal, on the complex oxide of the present invention for 100 parts by mass of the complex oxide, and then heat-treating the complex oxide in air at 1000°C for 25 hours. Specifically, the process is as follows. The complex oxide of the present invention is dispersed in an aqueous solution of a water-soluble rhodium salt (e.g., rhodium nitrate), the solvent is evaporated while stirring, and then the mixture is fired in air at 600°C for 1 hour to prepare a powder supporting 1 part by mass of rhodium element, calculated as metal, for 100 parts by mass of the complex oxide. The prepared powder is heat-treated in air at 1000°C for 25 hours to obtain the sample.

[0038] The oxidizing power of the composite oxide (300°C) is measured using a sample at 300°C. Specifically, the procedure is as follows: the sample is packed into a sample tube, heated to 800°C under an argon stream, and then cooled to 300°C. The oxidizing power of the composite oxide (300°C) is measured using the sample at 300°C thus obtained by carrying out the operation (A) described in the Examples.

[0039] The oxidizing power of the composite oxide (400°C) is measured using a sample at 400°C. Specifically, the procedure is as follows. After measuring the oxidizing power of the composite oxide (300°C), the sample is heated to 400°C under an argon stream. The thus obtained sample at 400°C is used to carry out the operation (A) described in the Examples to measure the oxidizing power of the composite oxide (400°C).

[0040] The oxidizing power of the composite oxide (500°C) is measured using a sample at 500°C. Specifically, the procedure is as follows. After measuring the oxidizing power of the composite oxide (400°C), the sample is heated to 500°C under an argon stream. The oxidizing power of the composite oxide (500°C) thus obtained is measured by carrying out the operation (A) described in the Examples using the sample at 500°C.

[0041] The composite oxide of the present invention can be used as a component of a catalyst for purifying exhaust gas.

[0042] In one embodiment, the exhaust gas purification catalyst comprises the composite oxide of the present invention and one or more kinds of precious metal elements supported on the composite oxide. The amounts of the composite oxide of the present invention and the precious metal elements contained in the exhaust gas purification catalyst can be appropriately adjusted.

[0043] The precious metal element can be selected from, for example, palladium, platinum, rhodium, etc. The precious metal element is supported on the composite oxide of the present invention in a form capable of functioning as a catalytically active component, for example, in the form of a precious metal, an alloy containing a precious metal element, a compound containing a precious metal element (for example, an oxide of a precious metal element), etc. The catalytically active component is preferably in the form of particles from the viewpoint of enhancing exhaust gas purification performance.

[0044] The exhaust gas purification catalyst may contain a carrier component for supporting a precious metal element. The carrier component is preferably a porous body. The carrier component may be selected from, for example, alumina, silica, silica-alumina, alumino-silicates, alumina-zirconia, alumina-chromia, alumina-ceria, etc.

[0045] The exhaust gas purifying catalyst may contain other components such as a stabilizer and a binder.

[0046] "Supported" means a state in which a precious metal element is physically or chemically adsorbed or held on the outer surface or the inner surface of a pore of the composite oxide of the present invention. Support of a precious metal element on the composite oxide of the present invention can be confirmed, for example, by the presence of the composite oxide of the present invention and the precious metal element in the same region in element mapping obtained by analyzing a cross section of an exhaust gas purification catalyst with an EDS (energy dispersive spectrometry).

[0047] In one embodiment, the exhaust gas purification catalyst is a molded body having a shape such as a pellet. The exhaust gas purification catalyst according to this embodiment can be produced, for example, by drying and calcining the exhaust gas purification catalyst composition. The drying temperature, drying time, calcination temperature and calcination time can be appropriately adjusted. Calcination can be carried out, for example, under air atmosphere.

[0048] In another embodiment, the exhaust gas purification catalyst comprises a substrate and a catalytic layer formed on the substrate, and the catalytic layer contains the composite oxide of the present invention and one or more kinds of precious metal elements supported on the composite oxide of the present invention.

[0049] The substrate can be appropriately selected from substrates used in known exhaust gas purification catalysts. The material of the substrate can be selected from ceramics such as alumina (Al2O3), mullite (3Al2O3-2SiO2), cordierite (2MgO-2Al2O3-5SiO2), aluminum titanate (Al2TiO5), silicon carbide (SiC), and metal materials such as stainless steel. The shape of the substrate can be selected from honeycomb, pellet, and spherical shapes. When using a honeycomb substrate, for example, a monolith substrate having a large number of parallel fine gas flow passages, i.e., channels, can be used so that a fluid flows inside the substrate.

[0050] The catalyst layer can be formed by applying the exhaust gas purification catalyst composition to the surface of the substrate, drying and firing. For example, when a monolithic substrate is used, the exhaust gas purification catalyst composition is applied to the inner wall surface of each channel of the monolithic substrate, followed by drying and firing to form a catalyst layer on the inner wall surface of each channel of the monolithic substrate. The catalyst layer can also be produced by a method in which the layer obtained by applying the exhaust gas purification catalyst composition to the substrate surface, drying and firing is impregnated with a solution containing a precious metal salt, followed by drying and firing. The drying temperature, drying time, firing temperature and firing time can be appropriately adjusted. The firing can be carried out, for example, under an air atmosphere.

[0051] The exhaust gas purification catalyst composition used in the production of the exhaust gas purification catalyst is, for example, a slurry containing the composite oxide of the present invention and a salt of a precious metal element. The salt of the precious metal element can be selected from, for example, a nitrate, an ammine complex salt, a chloride, etc. The solvent contained in the dispersion can be selected from, for example, water, an organic solvent, etc.

[0052] <Method for producing composite oxide> The composite oxide of the present invention can be produced by a method including steps (a) to (c), which will be described below.

[0053] Engineering (a) Step (a) is a step of preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt.

[0054] The water contained in the raw material liquid is preferably pure water such as ion-exchanged water. The raw material liquid may contain one or more solvents other than water. The solvent other than water can be selected from organic solvents such as alcohol, acetone, dimethyl sulfoxide, and dimethylformamide. The total amount of one or more solvents other than water is not particularly limited as long as the water-soluble salt can be dissolved in the raw material liquid, but is usually 50.0 vol% or less, preferably 20.0 vol% or less, based on the volume of the raw material liquid.

[0055] The cerium salt and the zirconium salt contained in the raw material liquid may be water-soluble or poorly water-soluble, but it is preferable that at least one of the cerium salt and the zirconium salt is a water-soluble salt, and it is more preferable that both of the cerium salt and the zirconium salt are water-soluble salts. The rare earth metal salt other than the cerium salt that is optionally contained in the raw material liquid may be a water-soluble salt or poorly water-soluble salt, but it is preferable that it is a water-soluble salt.

[0056] The solubility of a water-soluble salt in water at 20°C (the mass of a water-soluble salt that can be dissolved in 100 g of water at 20°C) is preferably 1.0 g or more, more preferably 2.0 g or more, and even more preferably 5.0 g or more, and the solubility of a poorly water-soluble salt in water at 20°C (the mass of a poorly water-soluble salt that can be dissolved in 100 g of water at 20°C) is preferably less than 1.0 g, more preferably 0.5 g or less, and even more preferably 0.1 g or less.

[0057] The water-soluble cerium salt can be selected from, for example, cerium chloride, cerium nitrate, cerium (III) sulfate, cerium acetate, etc., but cerium chloride is preferred from the viewpoint of preventing a decrease in the heat resistance of the composite oxide due to contamination with nitrate radicals, etc., and from the viewpoint of easy availability. The raw material liquid may contain two or more types of water-soluble cerium salts. The amount of the water-soluble cerium salt contained in the raw material liquid is appropriately adjusted so that the amount of cerium element contained in the composite oxide produced in step (c) calculated as cerium oxide falls within a desired range.

[0058] The poorly water-soluble cerium salt can be selected from, for example, cerium hydroxide, cerium oxide, cerium carbonate, cerium (IV) sulfate, etc., but when the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt and the raw material liquid becomes acidic), cerium hydroxide or cerium carbonate is preferred from the viewpoint of being soluble in the raw material liquid, and cerium hydroxide is more preferred. The raw material liquid may contain two or more types of poorly water-soluble cerium salts. The amount of the poorly water-soluble cerium salt contained in the raw material liquid is appropriately adjusted so that the amount of cerium element contained in the composite oxide produced in step (c) calculated as cerium oxide is within a desired range.

[0059] The water-soluble zirconium salt can be selected from, for example, zirconium oxychloride, zirconium chloride, zirconium oxynitrate, zirconium nitrate, zirconium oxyacetate, etc., but from the viewpoint of preventing a decrease in the heat resistance of the composite oxide due to contamination with nitrate radicals, etc., and from the viewpoint of easy availability, zirconium oxychloride or zirconium chloride is preferred, and zirconium oxychloride is more preferred. The raw material liquid may contain two or more types of water-soluble zirconium salts. The amount of the water-soluble zirconium salt contained in the raw material liquid is appropriately adjusted so that the amount of zirconium element contained in the composite oxide produced in step (c) calculated as zirconium oxide is within a desired range.

[0060] The water-insoluble zirconium salt can be selected from, for example, zirconium hydroxide, basic zirconium sulfate, zirconium oxide, basic zirconium carbonate, etc., but when the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt and the raw material liquid becomes acidic), zirconium hydroxide or basic zirconium carbonate is preferred from the viewpoint of being soluble in the raw material liquid, and zirconium hydroxide is more preferred from the viewpoint of excellent miscibility with aluminum compound particles. The raw material liquid may contain two or more types of water-insoluble zirconium salts. The amount of the water-insoluble zirconium salt contained in the raw material liquid is appropriately adjusted so that the amount of zirconium element contained in the composite oxide produced in step (c) calculated as zirconium oxide is within a desired range.

[0061] The water-soluble rare earth metal salt can be selected from, for example, chlorides, nitrates, sulfates, acetates, etc. of rare earth metal elements. From the viewpoint of preventing the deterioration of the heat resistance of the composite oxide due to the inclusion of nitrate ions, etc., and from the viewpoint of easy availability, chlorides of rare earth metal elements (e.g., lanthanum chloride, neodymium chloride, yttrium chloride, etc.) are preferred. The sulfates of rare earth metal elements are preferably sulfates of trivalent rare earth metal elements. The raw material liquid may contain two or more kinds of water-soluble rare earth metal salts. The type and amount of the water-soluble rare earth metal salt contained in the raw material liquid are appropriately adjusted so that the amount of the rare earth metal element contained in the composite oxide produced in step (c) in terms of oxide is within a desired range.

[0062] The poorly water-soluble rare earth metal salt can be selected from, for example, hydroxides, oxides, carbonates, etc. of rare earth metal elements. When the raw material liquid is acidic (for example, when an acid is generated by hydrolysis of a water-soluble rare earth metal salt, making the raw material liquid acidic), from the viewpoint of being soluble in the raw material liquid, hydroxides or carbonates of rare earth metal elements (for example, lanthanum hydroxide, neodymium hydroxide, yttrium hydroxide, lanthanum carbonate, neodymium carbonate, yttrium carbonate, etc.) are preferred, and hydroxides of rare earth metal elements are more preferred. The raw material liquid may contain two or more types of poorly water-soluble rare earth metal salts. The type and amount of the poorly water-soluble rare earth metal salt contained in the raw material liquid are appropriately adjusted so that the amount of the rare earth metal element contained in the composite oxide produced in step (c) in terms of oxide is within a desired range.

[0063] The aluminum compound particles can be selected from alumina particles and alumina hydrate particles. The aluminum compound particles may be composed of either alumina particles or alumina hydrate particles, or may be composed of both, but from the viewpoint of improving the heat resistance of the composite oxide produced in step (c), it is preferable that the aluminum compound particles are composed of alumina hydrate particles. Alumina hydrate particles have low sinterability and are easily finely dispersed in the composite oxide, which is advantageous in improving the heat resistance of the composite oxide.

[0064] The alumina hydrate constituting the alumina hydrate particles is preferably alumina monohydrate or alumina trihydrate, more preferably alumina monohydrate, from the viewpoint of improving the heat resistance of the composite oxide produced in step (c).

[0065] Alumina monohydrate is typically represented by a composition formula such as AlO(OH), α-Al2O3·H2O, etc. The alumina monohydrate can be selected from, for example, boehmite, diaspore, etc., but is preferably boehmite from the viewpoint of improving the heat resistance of the composite oxide produced in step (c). The boehmite may be so-called pseudo-boehmite, which contains one or more water molecules between layers.

[0066] Alumina trihydrate is typically represented by the formula Al(OH)3, Al2O3·3H2O, etc. The alumina trihydrate can be selected from, for example, gibbsite (also called hydrargillite), bayerite, etc.

[0067] Median diameter D of aluminum compound particles measured by dynamic light scattering method 50 is preferably 1 nm or more and 220 nm or less, more preferably 5 nm or more and 200 nm or less, even more preferably 10 nm or more and 160 nm or less, and even more preferably 15 nm or more and 100 nm or less. 50 When the amount of the aluminum compound particles is within the above range, the dispersibility of the aluminum compound particles in the precipitate formed in step (b) and in the composite oxide produced in step (c) can be improved, thereby improving the heat resistance of the composite oxide.

[0068] The median diameter D of aluminum compound particles measured by dynamic light scattering 50 " means a particle size at which the cumulative volume is 50% in the volume-based particle size distribution of aluminum compound particles measured by dynamic light scattering. Measurement of the volume-based particle size distribution of aluminum compound particles by dynamic light scattering can be carried out by dispersing the aluminum compound particles in pure water such as ion-exchanged water and using a commercially available particle size distribution measuring device (for example, "Zetasizer Nano ZS" manufactured by Malvern Panalytical).

[0069] From the viewpoint of obtaining a desired precipitate in step (b), it is preferable to stir the raw material liquid prepared in step (a) before subjecting it to step (b) to disperse the aluminum compound particles in the raw material liquid.

[0070] Engineering (b) Step (b) is a step of adding a precipitating agent to the raw material liquid prepared in step (a) to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium.

[0071] The raw material liquid prepared in step (a) contains metal ions generated by ionization of the water-soluble salt. The precipitant added to the raw material liquid causes the metal ions generated by ionization of the water-soluble salt to precipitate as a poorly water-soluble salt, and can be appropriately selected depending on the type of water-soluble salt contained in the raw material liquid and the type of poorly water-soluble salt to be precipitated.

[0072] When the raw material liquid contains a water-soluble cerium salt, a precipitant that precipitates cerium ions as a poorly water-soluble cerium salt can be used. The poorly water-soluble cerium salt to be precipitated can be selected from, for example, cerium hydroxide, cerium carbonate, etc., with cerium hydroxide being preferred. When the poorly water-soluble cerium salt to be precipitated is cerium carbonate, the carbonate ions used to form cerium carbonate may inhibit the formation of a precipitate of zirconium ions. For example, the carbonate ions may cause a water-soluble zirconium complex (e.g., [Zr(CO3)4] 4- , [ZrOH(CO3)3] 3- etc.) may be formed.

[0073] When the raw material liquid contains a water-soluble zirconium salt, a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt can be used. The poorly water-soluble zirconium salt to be precipitated can be selected from, for example, zirconium hydroxide, basic zirconium sulfate, etc., with zirconium hydroxide or basic zirconium sulfate being preferred, and zirconium hydroxide being more preferred.

[0074] When the raw material liquid contains a water-soluble rare earth metal salt, a precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts can be used. The poorly water-soluble rare earth metal salts to be precipitated can be selected from, for example, hydroxides and carbonates of rare earth metal elements, but are preferably hydroxides of rare earth metal elements (e.g., lanthanum hydroxide, neodymium hydroxide, yttrium hydroxide, etc.). When the poorly water-soluble rare earth metal salt to be precipitated is a carbonate of a rare earth metal element, the carbonate ions used for forming the carbonate may inhibit the formation of a precipitate of zirconium ions.

[0075] One type of precipitant may precipitate two or more types of metal ions as poorly water-soluble metal salts. Thus, the precipitant that precipitates cerium ions as poorly water-soluble cerium salts, the precipitant that precipitates zirconium ions as poorly water-soluble zirconium salts, and the precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts may be the same or different.

[0076] The precipitant may be selected from, for example, an aqueous solution containing sulfate ions and a compound that can be dissolved in water to generate sulfate ions. This precipitant can precipitate zirconium ions as basic zirconium sulfate. The compound that can be dissolved in water to generate sulfate ions may be selected from, for example, ammonium sulfate, sulfuric acid, an alkali metal sulfate, cerium (III) sulfate, a rare earth metal sulfate, etc., but from the viewpoint of increasing the uniformity of the solid solution phase (for example, a solid solution phase of cerium oxide and zirconium oxide) formed by cerium element, zirconium element, and oxygen element, and from the viewpoint of easy availability, ammonium sulfate, sulfuric acid, or an alkali metal sulfate is preferable. The rare earth metal sulfate is preferably a trivalent rare earth metal sulfate.

[0077] The precipitant may be selected from, for example, an aqueous solution containing hydroxide ions and a compound capable of dissolving in water to generate hydroxide ions. The precipitant can precipitate cerium ions, zirconium ions, and rare earth metal ions as cerium hydroxide, zirconium hydroxide, and hydroxides of rare earth metal elements, respectively. The compound capable of dissolving in water to generate hydroxide ions may be selected from, for example, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, lithium hydroxide, ammonia, amines, quaternary ammonium hydroxide, guanidine, alkali metal carbonates, alkali metal bicarbonates, urea, and the like, with sodium hydroxide being preferred. Sodium hydroxide is highly basic and easily available.

[0078] The pH of the raw material liquid (raw material liquid after adding the precipitant) when forming the precipitate can be appropriately adjusted, for example, from the viewpoint of suppressing the elution of components in the precipitate including cerium, zirconium, aluminum, and possibly rare earth metal elements other than cerium, it can be set to 9 or more and 14 or less.

[0079] By adding a precipitating agent to the raw material liquid prepared in step (a), a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium is formed.

[0080] The cerium element is contained in the precipitate in the form of a poorly water-soluble cerium salt. The poorly water-soluble cerium salt contained in the precipitate may be a poorly water-soluble cerium salt contained in the raw material liquid from the beginning, or may be a poorly water-soluble cerium salt formed by a precipitating agent. However, from the viewpoint of improving the dispersibility of the aluminum compound particles in the precipitate formed in step (b) and the composite oxide produced in step (c), thereby improving the heat resistance of the composite oxide, it is preferable that the poorly water-soluble cerium salt is a poorly water-soluble cerium salt formed by a precipitating agent.

[0081] The zirconium element is contained in the precipitate in the form of a poorly water-soluble zirconium salt. The poorly water-soluble zirconium salt contained in the precipitate may be a poorly water-soluble zirconium salt originally contained in the raw material liquid, or may be a poorly water-soluble zirconium salt formed by a precipitating agent, but is preferably a poorly water-soluble zirconium salt formed by a precipitating agent from the viewpoint of improving the dispersibility of aluminum compound particles in the precipitate formed in step (b) and the composite oxide produced in step (c), thereby improving the heat resistance of the composite oxide.

[0082] The rare earth metal element is contained in the precipitate in the form of a poorly water-soluble rare earth metal salt. The poorly water-soluble rare earth metal salt contained in the precipitate may be a poorly water-soluble rare earth metal salt originally contained in the raw material liquid, or may be a poorly water-soluble rare earth metal salt formed by a precipitant, but is preferably a poorly water-soluble rare earth metal salt formed by a precipitant from the viewpoint of improving the dispersibility of aluminum compound particles in the precipitate formed in step (b) and the composite oxide produced in step (c), thereby improving the heat resistance of the composite oxide.

[0083] The precipitate obtained in step (b) contains poorly water-soluble salt particles and aluminum compound particles in a mixed state. Examples of poorly water-soluble salt particles include composite salt particles containing poorly water-soluble cerium salt, poorly water-soluble zirconium salt, and occasionally poorly water-soluble rare earth metal salt other than poorly water-soluble cerium salt, poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles other than poorly water-soluble cerium salt particles, etc. From the viewpoint of improving the oxygen storage capacity of the composite oxide, it is preferable that the precipitate contains composite salt particles. The precipitate may contain poorly water-soluble cerium salt particles, poorly water-soluble zirconium salt particles, poorly water-soluble rare earth metal salt particles other than poorly water-soluble cerium salt particles, etc. in addition to the composite salt particles.

[0084] The precipitate obtained in step (b) is preferably in the form of a slurry or cake, more preferably in the form of a cake, before being subjected to step (c). The slurry or cake can be obtained by subjecting the raw material liquid subjected to step (b) to a solid-liquid separation method. The solid-liquid separation method can be selected from, for example, filtration, centrifugation, decantation, etc., but filtration is preferred from the viewpoints of ease of operation and excellent solid-liquid separation efficiency. Note that the solvent is not completely removed, so the solvent remains in the slurry or cake.

[0085] The precipitate obtained in step (b) is preferably washed with a washing liquid before being subjected to step (c). As the washing liquid, water (e.g., pure water such as ion-exchanged water) can be used. In addition, from the viewpoint of suppressing the elution of components in the precipitate and from the viewpoint of washing and removing sulfur content in the precipitate, a solution containing various sodium salts (sodium hydroxide, sodium carbonate, sodium bicarbonate, etc.), ammonia water, or a solution containing an acid (nitric acid, acetic acid, etc.) can be used as the washing liquid, and the pH of the washing liquid can be adjusted to, for example, 6 or more and 14 or less.

[0086] Engineering (c) Step (c) is a step of calcining the precipitate obtained in step (b) to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium.

[0087] The precipitate obtained in step (b) contains a mixture of poorly water-soluble salt particles (e.g., composite salt particles containing a poorly water-soluble cerium salt, a poorly water-soluble zirconium salt, and optionally a poorly water-soluble rare earth metal salt other than a poorly water-soluble cerium salt) and aluminum compound particles. Therefore, aluminum compound particles are present between the poorly water-soluble salt particles. When the precipitate obtained in step (b) is fired, the aluminum compound particles present between the poorly water-soluble salt particles suppress sintering of the poorly water-soluble salt particles. This improves the heat resistance of the composite oxide obtained in step (c), and the poorly water-soluble salt particles can be sintered to a temperature of 60.0m. 2It is possible to realize a specific surface area of ​​the composite oxide of 2.0 x 100 / g or more as measured by the BET method after heat treatment in air at 1000°C for 25 hours.

[0088] The precipitate can be calcined according to a conventional method. Calcination is usually carried out under air. The calcination temperature is usually 400°C to 1200°C, preferably 500°C to 1100°C, more preferably 600°C to 1000°C. The calcination time is usually 0.1 hours to 20 hours, preferably 0.5 hours to 10 hours, more preferably 1 hour to 5 hours.

[0089] The obtained composite oxide may be pulverized as necessary. The pulverization can be carried out according to a conventional method. For example, the pulverization can be carried out in a dry or wet manner using a mortar, a hammer mill, a ball mill, a bead mill, a jet mill, a roller mill, or the like.

[0090] Hereinafter, an embodiment of the method for producing a composite oxide will be described.

[0091] [First embodiment] In the first embodiment, in step (a), a raw material liquid is prepared in which the cerium salt, the zirconium salt, and the rare earth metal salt other than the cerium salt are all water-soluble salts. Note that the first embodiment also includes an embodiment in which the raw material liquid prepared in step (a) does not contain any rare earth metal salt other than the cerium salt, and in the embodiment in which the raw material liquid prepared in step (a) does not contain any rare earth metal salt other than the cerium salt, "the cerium salt, the zirconium salt, and the rare earth metal salt other than the cerium salt are all water-soluble salts" means that both the cerium salt and the zirconium salt are water-soluble salts.

[0092] In the first embodiment, in step (b), a precipitant that precipitates cerium ions as a poorly water-soluble cerium salt and a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt are used as precipitants added to the raw material liquid. In an embodiment in which the raw material liquid contains a rare earth metal salt, a precipitant that precipitates rare earth metal ions as a poorly water-soluble rare earth metal salt is also used. These precipitants may be the same type or different types.

[0093] In the first embodiment, in step (b), it is preferable to add a first precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions to the raw material liquid to form a first precipitate containing zirconium element and aluminum element, and then add a second precipitant selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions to the raw material liquid to form a second precipitate containing cerium element, zirconium element, aluminum element, and optionally rare earth metal element other than cerium element.

[0094] In the step (b), when a first precipitating agent is added to the raw material liquid, a first precipitate containing elemental zirconium and elemental aluminum is formed.

[0095] The zirconium element is contained in the first precipitate in the form of basic zirconium sulfate, which is a poorly water-soluble zirconium salt formed by the first precipitating agent.

[0096] The aluminum element is contained in the first precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble zirconium salt formed by the first precipitant.

[0097] The first precipitate contains basic zirconium sulfate particles and aluminum compound particles in a mixture.

[0098] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the heat resistance of the composite oxide produced in step (c), the temperature of the raw material liquid when the first precipitant is added is preferably 40°C or more and 150°C or less, more preferably 55°C or more and 130°C or less, and even more preferably 70°C or more and 100°C or less.

[0099] From the viewpoints of sufficiently precipitating basic zirconium sulfate, suppressing the adverse effects of excess sulfate ions, and improving the heat resistance of the composite oxide produced in step (c), it is preferable to add the first precipitant to the raw material liquid so that the molar amount of sulfate ions in the raw material liquid is 0.10 to 10 times the molar amount of zirconium element in the raw material liquid. The molar amount of sulfate ions in the raw material liquid is more preferably 0.20 to 5.0 times, and even more preferably 0.30 to 2.0 times, the molar amount of zirconium element in the raw material liquid.

[0100] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the heat resistance of the composite oxide produced in step (c), it is preferable to age the first precipitate while stirring the raw material liquid after adding the first precipitant. The ageing time is preferably 0.1 to 10 hours, more preferably 0.2 to 5 hours, and even more preferably 0.3 to 3 hours.

[0101] After the first precipitate is formed and aged as necessary, a second precipitating agent is added to the raw material liquid to form a second precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium.

[0102] The cerium element is contained in the second precipitate in the form of cerium hydroxide, which is a poorly water-soluble cerium salt formed by the second precipitating agent.

[0103] The zirconium element is contained in the second precipitate in the form of zirconium hydroxide. Zirconium hydroxide is a poorly water-soluble zirconium salt formed by the second precipitating agent. Note that basic zirconium sulfate formed by the first precipitating agent is converted to zirconium hydroxide by the second precipitating agent.

[0104] The rare earth metal element is contained in the second precipitate in the form of a hydroxide of the rare earth metal element. The hydroxide of the rare earth metal element is a poorly water-soluble rare earth metal salt formed by the second precipitating agent. The poorly water-soluble rare earth metal salt formed by the second precipitating agent is coprecipitated with the poorly water-soluble cerium salt formed by the second precipitating agent.

[0105] The aluminum element is contained in the second precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble cerium salt formed by the second precipitant and, in some cases, the poorly water-soluble rare earth metal salt formed by the second precipitant. Note that at least a portion of the aluminum compound particles contained in the first precipitate is usually contained as it is in the second precipitate.

[0106] The second precipitate contains composite salt particles containing cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements other than cerium hydroxide, and aluminum compound particles in a mixed state. The second precipitate may contain cerium hydroxide particles, zirconium hydroxide particles, hydroxide particles of rare earth metal elements, etc., in addition to the composite salt particles. The composite salt particles are formed, for example, by adhesion and growth of cerium hydroxide and / or hydroxides of rare earth metal elements other than cerium hydroxide formed by the second precipitating agent on the surface of basic zirconium sulfate formed by the first precipitating agent (the basic zirconium sulfate is converted to zirconium hydroxide by the second precipitating agent).

[0107] From the viewpoints of sufficiently precipitating the target hydroxides (cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements), preventing dissolution of the aluminum compound particles by hydroxide ions, and improving the heat resistance of the composite oxide produced in step (c), the temperature of the raw material liquid when the second precipitant is added is preferably 35°C or more and 60°C or less, more preferably 35°C or more and 55°C or less, and even more preferably 35°C or more and 45°C or less.

[0108] From the viewpoint of suppressing dissolution of the aluminum compound particles by hydroxide ions and improving the heat resistance of the composite oxide produced in step (c), it is preferable to add a second precipitant to the raw material liquid so that the molar amount of hydroxide ions in the raw material liquid is 2.0 to 10 times the molar amount of oxygen required to convert the cerium, zirconium, and rare earth metal elements other than cerium in the raw material liquid into oxides. The molar amount of hydroxide ions in the raw material liquid is more preferably 2.0 to 5.0 times, and even more preferably 2.0 to 3.0 times the molar amount of oxygen required to convert the cerium, zirconium, and rare earth metal elements other than cerium in the raw material liquid into oxides.

[0109] The molar amount (M) of elemental oxygen required to convert elemental cerium, zirconium, and rare earth metal elements other than cerium in the raw material solution into their oxides can be calculated by M = [(molar amount of elemental cerium) × 2] + [(molar amount of elemental zirconium) × 2] + [(molar amount of elemental cerium, praseodymium, and rare earth metal elements other than terbium) × 3 / 2] + [(molar amount of elemental praseodymium) × 11 / 6] + [(molar amount of elemental terbium) × 7 / 4].

[0110] From the viewpoint of sufficiently precipitating the target hydroxides (cerium hydroxide, zirconium hydroxide, and optionally hydroxides of rare earth metal elements) and improving the heat resistance of the composite oxide produced in step (c), it is preferable to age the second precipitate while stirring the raw material liquid after adding the second precipitant. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48 hours or less, and even more preferably 1 hour or more and 24 hours or less.

[0111] In the first embodiment, in step (c), it is preferable to calcinate the second precipitate obtained in step (b) to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium.

[0112] Second Embodiment In the second embodiment, in step (a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt other than the cerium salt are both water-soluble salts, and the zirconium salt is a poorly water-soluble salt. Note that the second embodiment also includes an embodiment in which the raw material liquid prepared in step (a) does not contain a rare earth metal salt other than the cerium salt, and in the embodiment in which the raw material liquid prepared in step (a) does not contain a rare earth metal salt other than the cerium salt, "both the cerium salt and the rare earth metal salt are water-soluble salts, and the zirconium salt is a poorly water-soluble salt" means that the cerium salt is a water-soluble salt and the zirconium salt is a poorly water-soluble salt.

[0113] In the second embodiment, a precipitant that precipitates cerium ions as poorly water-soluble cerium salts is used as the precipitant added to the raw material solution in step (b). In an embodiment in which the raw material solution contains a rare earth metal salt, a precipitant that precipitates rare earth metal ions as poorly water-soluble rare earth metal salts is also used. These precipitants may be the same type or different types.

[0114] In the second embodiment, in step (b), it is preferable to add a precipitant selected from an aqueous solution containing hydroxide ions and a compound that can dissolve in water to produce hydroxide ions to the raw material liquid, and form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium.

[0115] When a precipitating agent is added to the raw material liquid, a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and possibly rare earth metal elements other than elemental cerium is formed.

[0116] The cerium element is present in the precipitate in the form of cerium hydroxide, a sparingly water-soluble cerium salt formed by the precipitating agent.

[0117] The zirconium element is contained in the precipitate in the form of a poorly water-soluble salt contained in the raw material liquid from the beginning, or in the form of zirconium hydroxide. When the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is basic zirconium sulfate, the basic zirconium sulfate is converted to zirconium hydroxide by the precipitating agent. In this case, the zirconium element is contained in the precipitate in the form of zirconium hydroxide. When the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is zirconium hydroxide, the zirconium element is contained in the precipitate in the form of a poorly water-soluble salt (zirconium hydroxide) contained in the raw material liquid from the beginning.

[0118] The rare earth metal element is contained in the precipitate in the form of a hydroxide of the rare earth metal element. The hydroxide of the rare earth metal element is a poorly water-soluble rare earth metal salt formed by the precipitating agent. The poorly water-soluble rare earth metal salt formed by the precipitating agent is coprecipitated with the poorly water-soluble cerium salt formed by the precipitating agent.

[0119] The aluminum element is contained in the precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble cerium salt formed by the precipitant and, in some cases, the poorly water-soluble rare earth metal salt formed by the precipitant.

[0120] The precipitate contains composite salt particles containing cerium hydroxide, poorly water-soluble zirconium salt (when the poorly water-soluble zirconium salt contained in the raw material solution from the beginning is basic zirconium sulfate, basic zirconium sulfate is converted to zirconium hydroxide by the precipitant), and optionally hydroxide of a rare earth metal element other than cerium hydroxide, and aluminum compound particles in a mixed state. In addition to the composite salt particles, the precipitate may contain cerium hydroxide particles, poorly water-soluble zirconium salt particles, zirconium hydroxide particles, hydroxide particles of a rare earth metal element, etc. The composite salt particles are formed, for example, by the adhesion and growth of cerium hydroxide and / or hydroxide of a rare earth metal element other than cerium hydroxide formed by the precipitant on the surface of poorly water-soluble zirconium salt (when the poorly water-soluble zirconium salt contained in the raw material solution from the beginning is basic zirconium sulfate, basic zirconium sulfate is converted to zirconium hydroxide by the precipitant).

[0121] The above description regarding the temperature of the raw material liquid when the second precipitant is added in the first embodiment also applies to the temperature of the raw material liquid when the precipitant is added in the second embodiment.

[0122] The above description regarding the amount of the second precipitant added to the raw material liquid in the first embodiment (the above description regarding the molar amount of hydroxide ions in the raw material liquid) also applies to the amount of the precipitant added to the raw material liquid in the second embodiment (the molar amount of hydroxide ions in the raw material liquid).

[0123] In the second embodiment, "the molar amount of oxygen element required to convert cerium element, zirconium element, and rare earth metal element other than cerium element in the raw material liquid into oxides" means the molar amount of oxygen element required to convert cerium element, zirconium element, and rare earth metal element other than cerium element in the raw material liquid into oxides when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is converted to zirconium hydroxide by a precipitant (for example, when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is basic zirconium sulfate), and means the molar amount of oxygen element required to convert cerium element and rare earth metal element other than cerium element in the raw material liquid into oxides when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is not converted to zirconium hydroxide by a precipitant (for example, when the poorly water-soluble zirconium salt contained in the raw material liquid from the beginning is zirconium hydroxide).

[0124] From the viewpoint of sufficiently precipitating the target hydroxide (cerium hydroxide, optionally zirconium hydroxide, and optionally hydroxide of a rare earth metal element) and improving the heat resistance of the composite oxide produced in step (c), it is preferable to age the precipitate while stirring the raw material liquid after adding the precipitant. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48.0 hours or less, and even more preferably 1 hour or more and 24 hours or less.

[0125] In the second embodiment, in step (c), the precipitate obtained in step (b) is fired to produce a composite oxide containing cerium element, zirconium element, aluminum element, and optionally rare earth metal element other than cerium element.

[0126] Third embodiment In the third embodiment, in step (a), a raw material liquid is prepared in which the cerium salt and the rare earth metal salt other than the cerium salt are both poorly water-soluble salts, and the zirconium salt is a water-soluble salt. Note that the third embodiment also includes an embodiment in which the raw material liquid prepared in step (a) does not contain a rare earth metal salt other than the cerium salt, and in the embodiment in which the raw material liquid prepared in step (a) does not contain a rare earth metal salt other than the cerium salt, "both the cerium salt and the rare earth metal salt are poorly water-soluble salts, and the zirconium salt is a water-soluble salt" means that the cerium salt is a poorly water-soluble salt, and the zirconium salt is a water-soluble salt.

[0127] In the third embodiment, a precipitant that precipitates zirconium ions as a poorly water-soluble zirconium salt is used as the precipitant added to the raw material liquid in the step (b).

[0128] In the third embodiment, in step (b), it is preferable to add a precipitant selected from an aqueous solution containing sulfate ions and a compound that can be dissolved in water to produce sulfate ions to the raw material liquid to form a first precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, and then add a reagent selected from an aqueous solution containing hydroxide ions and a compound that can be dissolved in water to produce hydroxide ions to the raw material liquid to treat the first precipitate with hydroxide ions to form a second precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium.

[0129] In step (b), when a precipitating agent is added to the raw material liquid, a first precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium is formed.

[0130] The cerium element is contained in the first precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid.

[0131] The zirconium element is contained in the first precipitate in the form of basic zirconium sulfate, which is a poorly water-soluble zirconium salt formed by the precipitating agent.

[0132] The rare earth metal elements other than elemental cerium are contained in the first precipitate in the form of poorly water-soluble salts that were originally contained in the raw material liquid.

[0133] The aluminum element is contained in the first precipitate in the form of aluminum compound particles. The aluminum compound particles originate from the aluminum compound particles originally contained in the raw material liquid. The aluminum compound particles in the raw material liquid are coprecipitated with the poorly water-soluble zirconium salt formed by the precipitating agent.

[0134] The first precipitate contains, in a mixed state, a poorly water-soluble cerium salt, basic zirconium sulfate, aluminum compound particles, and optionally a poorly water-soluble rare earth metal salt other than a poorly water-soluble cerium salt.

[0135] The above description regarding the temperature of the raw material liquid when the first precipitant is added in the first embodiment also applies to the temperature of the raw material liquid when the precipitant is added in the third embodiment.

[0136] The above description regarding the amount of the first precipitant added to the raw material liquid in the first embodiment (the above description regarding the molar amount of sulfate ions in the raw material liquid) also applies to the amount of precipitant added to the raw material liquid in the third embodiment (the molar amount of sulfate ions in the raw material liquid).

[0137] From the viewpoint of sufficiently precipitating basic zirconium sulfate and improving the heat resistance of the composite oxide produced in step (c), it is preferable to age the first precipitate while stirring the raw material liquid after adding the precipitant. The ageing time is preferably 0.1 to 10 hours, more preferably 0.2 to 5 hours, and even more preferably 0.3 to 3 hours.

[0138] After the first precipitate is formed and aged as necessary, a reagent selected from an aqueous solution containing hydroxide ions and a compound that can dissolve in water to produce hydroxide ions is added to the raw material liquid to treat the first precipitate with hydroxide ions, thereby forming a second precipitate containing cerium, zirconium, aluminum, and, in some cases, rare earth metal elements other than cerium.

[0139] The cerium element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid, or in the form of cerium hydroxide. When the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium oxide, cerium carbonate, or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions. In this case, the cerium element is contained in the second precipitate in the form of cerium hydroxide. When the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium hydroxide, the cerium element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid (the form of cerium hydroxide).

[0140] The zirconium element is contained in the second precipitate in the form of zirconium hydroxide. Zirconium hydroxide is a poorly water-soluble zirconium salt formed by hydroxide ions. Note that basic zirconium sulfate formed by the precipitating agent is converted to zirconium hydroxide by hydroxide ions.

[0141] The rare earth metal element is contained in the second precipitate in the form of a poorly water-soluble salt that was originally contained in the raw material liquid, or in the form of a hydroxide. If the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is an oxide or a carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of the rare earth metal element by hydroxide ions. In this case, the rare earth metal element is contained in the second precipitate in the form of a hydroxide. If the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is a hydroxide of the rare earth metal element, the rare earth metal element is contained in the second precipitate in the form of a poorly water-soluble salt (hydroxide) that was originally contained in the raw material liquid.

[0142] The aluminum element is contained in the second precipitate in the form of aluminum compound particles. The aluminum compound particles are derived from the aluminum compound particles originally contained in the raw material liquid. Note that at least a portion of the aluminum compound particles contained in the first precipitate is usually contained in the second precipitate as it is.

[0143] The second precipitate contains composite salt particles containing a poorly water-soluble cerium salt (when the poorly water-soluble cerium salt originally contained in the raw material liquid is cerium oxide, cerium carbonate or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions), zirconium hydroxide and, in some cases, a poorly water-soluble rare earth metal salt other than the poorly water-soluble cerium salt (when the poorly water-soluble rare earth metal salt originally contained in the raw material liquid is an oxide or carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of a rare earth metal element by hydroxide ions), and aluminum compound particles in a mixed state. In addition to the composite salt particles, the second precipitate may contain poorly water-soluble cerium salt particles, cerium hydroxide particles, zirconium hydroxide particles, poorly water-soluble rare earth metal salt particles, hydroxide particles of a rare earth metal element, etc. The composite salt particles are formed, for example, by the adhesion and growth of a poorly water-soluble cerium salt (if the poorly water-soluble cerium salt originally contained in the raw material liquid was cerium oxide, cerium carbonate, or cerium (IV) sulfate, the poorly water-soluble cerium salt is converted to cerium hydroxide by hydroxide ions) and / or a poorly water-soluble rare earth metal salt other than a poorly water-soluble cerium salt (if the poorly water-soluble rare earth metal salt originally contained in the raw material liquid was an oxide or carbonate, the poorly water-soluble rare earth metal salt is converted to a hydroxide of the rare earth metal element by hydroxide ions) on the surface of basic zirconium sulfate formed by the precipitant (the basic zirconium sulfate is converted to zirconium hydroxide by hydroxide ions).

[0144] The above description regarding the temperature of the raw material liquid when the second precipitant is added in the first embodiment also applies to the temperature of the raw material liquid when the reagent is added in the third embodiment.

[0145] The above explanation regarding the amount of the second precipitant added to the raw material liquid in the first embodiment (the above explanation regarding the molar amount of hydroxide ions in the raw material liquid) also applies to the amount of reagent added to the raw material liquid in the third embodiment (the molar amount of hydroxide ions in the raw material liquid).

[0146] In the third embodiment, "the molar amount of oxygen element required to convert cerium element, zirconium element, and rare earth metal elements other than cerium element in the raw material solution into oxides" means the molar amount of oxygen element required to convert cerium element, zirconium element, and rare earth metal elements other than cerium element in the raw material solution into oxides in the case where the poorly water-soluble cerium salt and the poorly water-soluble rare earth metal salt originally contained in the raw material solution are converted into cerium hydroxide and hydroxides of rare earth metal elements, respectively, by the reagent, and means the molar amount of oxygen element required to convert cerium element, zirconium element, and rare earth metal elements other than cerium element in the raw material solution into oxides in the case where the poorly water-soluble cerium salt originally contained in the raw material solution is converted into zirconium hydroxide by the reagent, and the poorly water-soluble rare earth metal salt originally contained in the raw material solution is not converted into hydroxides of rare earth metal elements by the reagent. The term "oxygen" refers to the molar amount of oxygen required to convert the cerium element and the zirconium element in the raw material solution into their oxides when the poorly water-soluble cerium salt originally contained in the raw material solution is not converted to zirconium hydroxide by the reagent and the poorly water-soluble rare earth metal salt originally contained in the raw material solution is converted to a hydroxide of the rare earth metal element by the reagent, and refers to the molar amount of oxygen required to convert the zirconium element and the rare earth metal element other than the cerium element in the raw material solution into their oxides when the poorly water-soluble cerium salt and the poorly water-soluble rare earth metal salt originally contained in the raw material solution are not converted to zirconium hydroxide and a hydroxide of the rare earth metal element by the reagent, respectively.

[0147] From the viewpoint of sufficiently precipitating the target hydroxides (zirconium hydroxide, cerium hydroxide, and optionally hydroxides of rare earth metal elements) and improving the heat resistance of the composite oxide produced in step (c), it is preferable to age the second precipitate while stirring the raw material liquid after adding the reagents. The ageing time is preferably 1 hour or more and 96 hours or less, more preferably 1 hour or more and 48 hours or less, and even more preferably 1 hour or more and 24 hours or less.

[0148] In the third embodiment, in step (c), the second precipitate obtained in step (b) is calcined to produce a composite oxide containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium. EXAMPLES

[0149] [Examples 1 to 5] (1) Manufacturing of composite oxide powder Cerium chloride (cerium oxide equivalent: 3.3 g), zirconium oxychloride (zirconium oxide equivalent: 14.7 g), lanthanum chloride (lanthanum oxide equivalent: 0.8 g), neodymium chloride (neodymium oxide equivalent: 0.8 g), and yttrium chloride (yttrium oxide equivalent: 0.8 g) were dissolved in pure water to obtain an aqueous solution with a total mass of 503.5 g.

[0150] The resulting aqueous solution was treated with a sol having a median diameter D 50 The boehmite particles (AlO(OH), Al2O3 equivalent amount 19.6 g) having the above structure were added and stirred to disperse the boehmite particles. Thus, a raw material liquid was obtained.

[0151] Median diameter of boehmite particles D 50 means the particle size at which the cumulative volume is 50% in the volume-based particle size distribution of boehmite particles measured by dynamic light scattering. The volume-based particle size distribution of boehmite particles measured by dynamic light scattering was measured by dispersing the boehmite particles in pure water (boehmite particle concentration: 1 mass%) and using a commercially available particle size distribution measuring device ("Zetasizer Nano ZS" manufactured by Malvern Panalytical).

[0152] The raw material liquid was heated to 85°C, and 58.7 g of a 25% by mass aqueous solution of ammonium sulfate was added dropwise while stirring the raw material liquid. After the dropwise addition was completed, the precipitate was aged at 85°C while stirring the raw material liquid. After the dropwise addition was completed, 118.6 g of a 25% by mass aqueous solution of sodium hydroxide was added dropwise while stirring the raw material liquid. After the dropwise addition was completed, the precipitate was aged to obtain a slurry.

[0153] The obtained slurry was subjected to suction filtration, and the precipitate was collected as a cake, which was then washed with pure water.

[0154] The washed cake was fired in an electric furnace, and the fired mass was pulverized to obtain a powder of a composite oxide containing elemental zirconium, elemental cerium, elemental lanthanum, elemental neodymium, elemental yttrium, and elemental aluminum.

[0155] The mass ratio (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum contained in the obtained composite oxide powder in terms of oxide was 36.8:8.2:2.0:2.0:2.0:49.0. The amount of each metal element contained in the composite oxide powder in terms of oxide was calculated from the amount of each metal element measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) (the same applies below).

[0156] (2) Measurement of the specific surface area of ​​composite oxide powder The composite oxide powders of Examples 1 to 5 obtained in (1) above were heat-treated in air at 1000°C for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0157] The specific surface area was measured according to "(3.5) Multipoint method" in "6.1 Quantitative method" of JIS R1626:1996 "Measurement method for specific surface area of ​​fine ceramic powder by gas adsorption BET method". Nitrogen, an adsorption gas, was used as the gas, and measurements were performed at five points within the equilibrium relative pressure range of 0.05 to 0.35. The measurement device used was Microtrack Bell's "BELSORP-miniX".

[0158] (3) Measurement of the oxidation power of complex oxides The composite oxide oxidizing power of the composite oxide powder of Example 1 obtained in (1) above was measured. The results are shown in Table 2.

[0159] The oxidizing power of the composite oxide was measured as follows. The composite oxide powder was dispersed in an aqueous rhodium nitrate solution, and the solvent was evaporated while stirring. The powder was then calcined in air at 600°C for 1 hour to obtain a powder carrying 1 part by mass of rhodium element in metal equivalent per 100 parts by mass of the composite oxide. The obtained powder was heat-treated in air at 1000°C for 25 hours to obtain a sample. The sample was packed in a sample tube, heated to 800°C under an argon stream, and then cooled to 300°C. The oxidizing power of the composite oxide (hereinafter referred to as "oxidizing power of the composite oxide (300°C)") was calculated using the sample at 300°C obtained in this manner by the following operation (A).

[0160] [Operation(A)] Oxygen was passed through the sample tube, followed by helium, and then a mixed gas (1 atm, 0°C) containing 25% by volume of CO and 75% by volume of helium was passed through 15 times at a flow rate of 50cc / min to reduce CeO2 and Rh2O3 contained in the sample. The amount of CO contained in the gas after contact was measured, and the amount of CO reduction (μmol) was calculated. The measurement device used was "BELMETAL" manufactured by Microtrack-Bell. Using the amount of CO reduction calculated by the above procedure, the oxidation power of the composite oxide was calculated based on the following formula. The oxidation power of the composite oxide is an index that indicates the ease of reduction of the composite oxide (i.e., the oxidation power of the composite oxide). Oxidizing power of composite oxide = CO reduction amount (μmol) / CeO2 content in composite oxide (g)

[0161] Using the oxidizing power of the complex oxide as an index, the oxygen storage and release capacity of the complex oxide after heat resistance can be evaluated. That is, when a CO / helium mixed gas is contacted with a complex oxide carrying rhodium element as described above, the following reactions occur: (1) 2CeO2+CO→Ce2O3+CO2, and (2) Rh2O3+3CO→2Rh+3CO2. Here, reaction (2) is a reaction that proceeds regardless of the oxygen storage and release capacity of the complex oxide. Therefore, by measuring the amount of CO reduction as described above, the amount of reaction (1) by the complex oxide (i.e., the oxygen storage and release capacity of the complex oxide) can be evaluated.

[0162] After measuring the oxidizing power of the composite oxide (300°C), the sample was heated to 400°C under an argon stream. The above-mentioned operation (A) was carried out using the thus obtained sample at 400°C to calculate the oxidizing power of the composite oxide (hereinafter referred to as "oxidizing power of the composite oxide (400°C)").

[0163] After measuring the oxidizing power of the composite oxide (400°C), the sample was heated to 500°C under an argon stream. The above-mentioned operation (A) was carried out using the thus obtained sample at 500°C to calculate the oxidizing power of the composite oxide (hereinafter referred to as "oxidizing power of the composite oxide (500°C)").

[0164] Example 6 The same operation as in Example 1 was carried out, except that the mass ratio (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the composite oxide powder was changed to 26.8:8.2:2.0:2.0:5.0:56.0. The obtained composite oxide powder was heat-treated in air at 1000°C for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0165] Example 7 The same operation as in Example 1 was carried out, except that the mass ratio (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the composite oxide powder was changed to 26.8:8.2:0:7.0:2.0:56.0. The obtained composite oxide powder was heat-treated in air at 1000°C for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0166] Comparative Example 1 Pure water was added to an alumina colloidal solution containing boehmite particles of about 10 nm (Aluminasol 520 manufactured by Nissan Chemical Industries, Ltd., equivalent to 19.6 g of Al2O3) to obtain an acidic colloidal solution with a total mass of 245 g.

[0167] Separately from the above acidic colloidal solution, cerium nitrate hexahydrate (CeO2 equivalent amount 3.3g), zirconium oxynitrate solution (ZrO2 equivalent amount 14.7g), lanthanum nitrate (La2O3 equivalent amount 0.8g), neodymium nitrate (Nd2O3 equivalent amount 0.8g) and yttrium nitrate (Y2O3 equivalent amount 0.8g) were dissolved in pure water to obtain an aqueous solution with a total mass of 364.1g. 28% by mass ammonia water was added to the obtained aqueous solution to adjust the pH to 4.

[0168] The above two solutions were mixed to obtain a slurry. The obtained slurry was dried in air at 300°C for 10 hours, and then fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements.

[0169] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the obtained composite oxide powder (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) calculated as oxide was 36.8:8.2:2.0:2.0:2.0:49.0.

[0170] The obtained composite oxide powder was heat-treated in air at 1000° C. for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0171] Comparative Example 2 Ammonium cerium (IV) nitrate (CeO2 equivalent: 3.3 g), zirconium oxynitrate solution (ZrO2 equivalent: 14.7 g), lanthanum nitrate (La2O3 equivalent: 0.8 g), neodymium nitrate (Nd2O3 equivalent: 0.8 g), and yttrium nitrate (Y2O3 equivalent: 0.8 g) were dissolved in pure water to obtain an aqueous solution with a total mass of 218 g. The obtained aqueous solution was heated to 90°C.

[0172] Next, Disperal HP14 / 7 (citric acid modified boehmite particles, Al2O3 equivalent amount 19.6 g) was added to pure water and stirred, and 28 mass % ammonia water was added to adjust the pH to 10, obtaining a suspension with a total mass of 245 g.

[0173] The obtained suspension was slowly dropped into the above aqueous solution, and after completion of the dropwise addition, 28% by mass ammonia water was added to adjust the pH to 8.7. After stirring at 90°C for 30 minutes, the mixture was filtered, and the obtained cake was washed with pure water at 60°C. The washed cake was dried overnight at 120°C and then fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing zirconium, cerium, lanthanum, neodymium, yttrium, and aluminum elements.

[0174] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the obtained composite oxide powder (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) calculated as oxide was 36.8:8.2:2.0:2.0:2.0:49.0.

[0175] The obtained composite oxide powder was heat-treated in air at 1000° C. for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0176] Comparative Example 3 Cerium nitrate hexahydrate (CeO2 equivalent: 3.3 g), zirconium oxynitrate solution (ZrO2 equivalent: 14.7 g), lanthanum nitrate (La2O3 equivalent: 0.8 g), neodymium nitrate (Nd2O3 equivalent: 0.8 g), and yttrium nitrate (Y2O3 equivalent: 0.8 g) were dissolved in pure water to obtain an aqueous solution with a total mass of 216.1 g.

[0177] While stirring the obtained aqueous solution, 18% by mass ammonia water was added dropwise to adjust the pH to 3. After adding 1.5 g of 30% by mass hydrogen peroxide water, 18% by mass ammonia water was further added dropwise until the pH reached 7.25. After that, the mixture was stirred for 30 minutes to obtain a slurry. The obtained slurry was filtered, and the obtained cake was washed with pure water.

[0178] The cake was added with pure water to be slurried again, and a total mass of 300 g of slurry was obtained. 28% by mass of ammonia water was dropped into the obtained slurry to adjust the pH to 9.5, and then stirred for 30 minutes. The slurry was filtered, and 31.1 g of a surfactant (Newcoal 564, manufactured by Nippon Nyukazai Co., Ltd.) was impregnated into the obtained cake. Disperal HP14 (boehmite particles, Al2O3 equivalent amount 19.6 g) was suspended in pure water to obtain a suspension of 450 g in total mass, and the impregnated cake was added while stirring, and slurried again. The obtained slurry was filtered, and the obtained cake was dried at 120 ° C overnight, and then fired in an electric furnace. The fired lump was pulverized to obtain a powder of a composite oxide containing zirconium element, cerium element, lanthanum element, neodymium element, yttrium element, and aluminum element.

[0179] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the obtained composite oxide powder (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) calculated as oxide was 36.8:8.2:2.0:2.0:2.0:49.0.

[0180] The obtained composite oxide powder was heat-treated in air at 1000° C. for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0181] The composite oxide powder thus obtained was measured for composite oxide oxidizing power (300° C.), composite oxide oxidizing power (400° C.), and composite oxide oxidizing power (500° C.) in the same manner as above. The results are shown in Table 2.

[0182] Comparative Example 4 Cerium nitrate hexahydrate (CeO2 equivalent: 3.3 g), zirconium oxynitrate solution (ZrO2 equivalent: 14.7 g), lanthanum nitrate (La2O3 equivalent: 0.8 g), neodymium nitrate (Nd2O3 equivalent: 0.8 g), and yttrium nitrate (Y2O3 equivalent: 0.8 g) were dissolved in pure water to obtain an aqueous solution with a total mass of 116.3 g. A suspension with a total mass of 122 g obtained by dispersing Disperal 23N4-80 (boehmite particles, Al2O3 equivalent: 19.6 g) in pure water was added to the obtained aqueous solution, and then 10.3 g of 30% by mass hydrogen peroxide solution was added and the mixture was stirred for 5 minutes.

[0183] Separately from the above mixture, 18% by mass ammonia water was charged in a beaker, and the above mixture was dropped over 1 hour while stirring. The precipitate was collected by filtration and washed with pure water to remove nitrates. The cake obtained by filtration was added to pure water to form a slurry again, and a total mass of 400 g of slurry was obtained. 28% by mass ammonia water was added to the obtained slurry, the pH was adjusted to 10, and then hydrothermal treatment was performed at 150 ° C for 10 hours. After the hydrothermal treatment, 12 g of lauric acid was added over 1 hour while stirring at 70 ° C. The solid was collected by filtration and washed with pure water. The obtained cake was dried overnight at 120 ° C, and then fired in an electric furnace. The fired mass was pulverized to obtain a powder of a composite oxide containing zirconium element, cerium element, lanthanum element, neodymium element, yttrium element, and aluminum element.

[0184] The mass ratio of zirconium, cerium, lanthanum, neodymium, yttrium and aluminum elements contained in the obtained composite oxide powder (ZrO2:CeO2:La2O3:Nd2O3:Y2O3:Al2O3) calculated as oxide was 36.8:8.2:2.0:2.0:2.0:49.0.

[0185] The obtained composite oxide powder was heat-treated in air at 1000° C. for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0186] [Comparative Examples 5 to 13] Except for changing the aluminum element source as shown in Table 1, the same procedures as in Examples 1 to 5 were carried out to obtain composite oxide powders.

[0187] The obtained composite oxide powder was heat-treated in air at 1000° C. for 25 hours, and the specific surface area of ​​the heat-treated composite oxide powder was measured by the BET method. The results are shown in Table 1.

[0188] The composite oxide oxidizing power (300° C.), composite oxide oxidizing power (400° C.), and composite oxide oxidizing power (500° C.) of the composite oxide powders of Comparative Examples 12 and 13 were measured in the same manner as above. The results are shown in Table 2.

[0189] [Table 1]

[0190] As shown in Table 1, the specific surface area of ​​the composite oxides of Examples 1 to 5 measured by the BET method after heat treatment in air at 1000° C. for 25 hours was 60 m 2 / g or more, whereas the specific surface areas of the composite oxides of Comparative Examples 1 to 13 measured by the BET method after heat treatment in air at 1000°C for 25 hours were 60 m 2 This indicates that the heat resistance of the composite oxides of Examples 1 to 5 is improved over that of the composite oxides of Comparative Examples 1 to 13.

[0191] [Table 2]

[0192] As shown in Table 2, the result of Example 1 regarding the oxidation power of the composite oxide after heat treatment in air at 1000°C for 25 hours was superior to any of Comparative Examples 3, 12, and 13. That is, it was shown that the composite oxide prepared by the method of Example 1 has a superior oxygen storage and release ability after heat resistance than the composite oxides prepared by conventional methods such as Comparative Examples 3, 12, and 13.

Claims

1. The following steps: (a) preparing a raw material liquid containing water, a cerium salt, a zirconium salt, aluminum compound particles, and optionally a rare earth metal salt other than the cerium salt; (b) adding a precipitant to the raw material liquid to form a precipitate containing elemental cerium, elemental zirconium, elemental aluminum, and optionally rare earth metal elements other than elemental cerium; (c) A step of calcining the precipitate to produce a composite oxide containing cerium, zirconium, aluminum, and optionally rare earth metal elements other than cerium. A method for producing a complex oxide, comprising: the aluminum compound particles are boehmite particles, The median diameter D of the aluminum compound particles measured by dynamic light scattering method 50 is 1 nm or more and 220 nm or less.

2. 2. The method according to claim 1, wherein the cerium salt, the zirconium salt and the rare earth metal salt other than the cerium salt are all water-soluble salts.

3. In step (b), a first precipitant selected from an aqueous solution containing sulfate ions and a compound capable of dissolving in water to generate sulfate ions is added to the raw material liquid to form a first precipitate containing zirconium element and aluminum element, and then a second precipitant selected from an aqueous solution containing hydroxide ions and a compound capable of dissolving in water to generate hydroxide ions is added to the raw material liquid to form a second precipitate containing cerium element, zirconium element, aluminum element, and optionally rare earth metal element other than cerium element; The method according to claim 2 , wherein in step (c), the second precipitate is calcined to produce the composite oxide.

4. 4. The method according to claim 3, wherein in the step (b), the first precipitant is added to the raw material solution so that a molar amount of sulfate ions in the raw material solution is 0.10 to 10 times a molar amount of zirconium element in the raw material solution.

5. 5. The method according to claim 3, wherein in step (b), the second precipitant is added to the raw material solution so that a molar amount of hydroxide ions in the raw material solution is 2.0 to 10 times a molar amount of oxygen necessary for converting elemental cerium, elemental zirconium, and rare earth metal elements other than cerium in the raw material solution into oxides.

6. 2. The method according to claim 1, wherein the cerium salt and the rare earth metal salt other than the cerium salt are both water-soluble salts, and the zirconium salt is a poorly water-soluble salt.

7. In step (b), a precipitant selected from an aqueous solution containing hydroxide ions and a compound capable of dissolving in water to generate hydroxide ions is added to the raw material liquid to form a precipitate containing cerium element, zirconium element, aluminum element, and optionally rare earth metal element other than cerium element; The method according to claim 6 , wherein in the step (c), the precipitate is calcined to produce the composite oxide.

8. 8. The method according to claim 7, wherein in step (b), the precipitant is added to the raw material solution so that a molar amount of hydroxide ions in the raw material solution is 2.0 to 10 times a molar amount of oxygen necessary for converting elemental cerium, elemental zirconium, and rare earth metal elements other than cerium in the raw material solution into oxides.

9. 2. The method according to claim 1, wherein the cerium salt and the rare earth metal salt other than the cerium salt are both poorly water-soluble salts, and the zirconium salt is a water-soluble salt.

10. In step (b), a precipitant selected from an aqueous solution containing sulfate ions and a compound capable of dissolving in water to produce sulfate ions is added to the raw material liquid to form a first precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, and then a reagent selected from an aqueous solution containing hydroxide ions and a compound capable of dissolving in water to produce hydroxide ions is added to the raw material liquid to treat the first precipitate with hydroxide ions to form a second precipitate containing cerium, zirconium, aluminum, and optionally a rare earth metal element other than cerium, The method according to claim 9 , wherein in step (c), the second precipitate is calcined to produce the composite oxide.

11. 11. The method according to claim 10, wherein in the step (b), the precipitant is added to the raw material solution so that a molar amount of sulfate ions in the raw material solution is 0.10 to 10 times a molar amount of zirconium element in the raw material solution.

12. 12. The method according to claim 10, wherein in step (b), the reagent is added to the raw material solution so that a molar amount of hydroxide ions in the raw material solution is 2.0 to 10 times a molar amount of oxygen element required for converting cerium element, zirconium element, and rare earth metal elements other than cerium element in the raw material solution into oxides.

Citation Information

Patent Citations

  • Preparation method of high performance cerium zirconium aluminum oxygen-storage material

    CN102716733A

  • Production of catalyst for purifying exhaust gas

    JP1989123636A

  • Zirconium-cerium based compound oxide and manufacture of the same

    JP2000319019A

  • Manufacturing method for zirconia / ceria-based composite oxide

    JP2003137550A

  • Multiple oxide, its production method and catalyst for exhaust gas purification

    JP2006169021A